Intimate partner violence during lockdown in Tuscany, Italy: Economic or confinement-related shocks? - Francesca Bettio; Fernando Flores Tavares; Elisa Ticci (PLoS ONE, 2026)
We revisit the issue of Intimate Partner Violence (IPV) during the COVID-19 pandemic asking three questions: whether IPV worsened with lockdown, what pandemic-specific ‘shocks’ had the greatest impact, and how the results change when different measures of IPV are used. The large telephone survey we leveraged for this purpose was conducted in 2021 in the Italian region of Tuscany as part of a mixed-method research project on IPV during the first lockdowns, and it is, to our knowledge, the only (locally) representative survey on IPV during lockdowns conducted in Italy. Subjective evidence from the survey shows that, on balance, IPV worsened in frequency or severity or both. Econometric evidence suggests that parental overburden due to the presence of minors had the largest influence, followed by job loss, whereas we were not able to discern a significant influence for confinement in crowded space lacking privacy. Finally, and unsurprisingly, we found that using a fuzzy measure of violence outcomes that accounts for severity and intensity as well as prevalence of violence allows us to discern between shocks like job loss that primarily influenced the occurrence of violence without significantly influencing its harshness. Our empirical strategy principally relies on the exogeneity of pandemic-specific shocks to attribute causal interpretation to our estimates. However, our dependent variables (IPV outcomes) are binary or fractional, and endogeneity of some control covariates cannot be ruled out. To address these issues, we estimate average marginal effects using a two-step Control function (CF) approach combined with a quasi-likelihood method.